2019
DOI: 10.1109/tns.2019.2908174
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Quenching and Charge-Sharing Effects on Heavy-Ion Microbeam Induced ASET in a Full-Custom CMOS OpAmp

Abstract: In this work, charge sharing effects on Analog Single Event Transients are experimentally observed in a fully-custom designed, 180nm CMOS Operational Amplifier by means of a heavy-ion microbeam. Sensitive nodes of the differential stage showed bipolar output transients that cannot be explained by single node collection for the closed loop characteristics of the circuit under test. Layout of these transistors are consistent with charge sharing effects due to deposited charge diffusion. Implementation of linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…As shown in figure 7, the pulse quenching between the adjacent PMOSs depends on charge sharing collection, which can be classified into diffusion and bipolar amplification effect [15]. The diffusion process distributes the excess carriers throughout well/substrate and all of the adjacent nodes have the opportunity to collect the charges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in figure 7, the pulse quenching between the adjacent PMOSs depends on charge sharing collection, which can be classified into diffusion and bipolar amplification effect [15]. The diffusion process distributes the excess carriers throughout well/substrate and all of the adjacent nodes have the opportunity to collect the charges.…”
Section: Discussionmentioning
confidence: 99%
“…Sensitive node active charge cancellation (SNACC) technique [13,14] utilizes charge sharing to compensate injected charge at critical nodes in analog and mixed-signal circuits, which causes large area penalty and complicates system's design. Fontana et al [15] experimentally observed charge sharing between paired transistors in operational amplifier and provided linear modeling to simplify emulate simultaneous charge collection in differential data path.…”
Section: Introductionmentioning
confidence: 99%
“…The astronomy applications have been ruled by semiconductor based devices that are mostly susceptible to radiation phenomenon. The SEE investigation have been done in the previous literatures such as full-custom CMOS op-amp, Delta-Sigma modulators, Comparators, DC/DC power converters, high-speed current feedback amplifier [10][11][12][13][14]. A new scaling trend allows the RF CMOS technology to work in the giga-hertz of range applications, which is used to compete with other technology contenders, for instance SiGe, BiCMOS and III-IV technology.…”
Section: Introductionmentioning
confidence: 99%